2013
DOI: 10.1177/0003319713486536
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate is Associated With Burden of Coronary Atherosclerosis in Patients With Acute Coronary Syndrome

Abstract: We aimed to elucidate the relationship between mild to moderate renal impairements and burden of atherosclerosis in patients with acute coronary syndrome (ACS). A total of 380 patients with ACS were included in the study. Gensini and SYNTAX scores were also calculated. Kidney function was classified based on estimated glomerular filtration rate (eGFR) into stage 1: eGFR >90, stage 2: 60 to 89, and stage 3: 30 to 60 mL/min per 1.73 m(2). Gensini and SYNTAX scores were higher in stages 2 and 3 than in stage 1. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In our study, multivariate regression analysis revealed that eGFR was negatively associated with Gensini score, which is in accordance with previous studies [24,25]. Further analysis indicated that decreasing risks of triple-vessel disease and high Gensini score were shown in increasing quartiles of PA in patients with eGFR ≥90 ml/min/1.73 m 2 , but the interactive relationships were not significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, multivariate regression analysis revealed that eGFR was negatively associated with Gensini score, which is in accordance with previous studies [24,25]. Further analysis indicated that decreasing risks of triple-vessel disease and high Gensini score were shown in increasing quartiles of PA in patients with eGFR ≥90 ml/min/1.73 m 2 , but the interactive relationships were not significant.…”
Section: Discussionsupporting
confidence: 91%
“…Impaired renal function is associated with not only the prevalence of CAD, but also the severity of atherosclerotic burden in patients with suspected CAD or confirmed ACS, as reflected by Gensini score and SYNTAX score [24,25], which is another scoring system used to assess coronary stenosis. In our study, multivariate regression analysis revealed that eGFR was negatively associated with Gensini score, which is in accordance with previous studies [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IGFR have more burden of coronary atherosclerosis in patients with ACS [17]. Although there is no particular reason not to treat IGFR patients just like patients without renal dysfunction, physicians prescribed fewer guideline-recommended treatments even in the absence of contraindications [18].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation of SS with “softer” end-points (estimated glomerular filtration rate (eGFR) in stable CAD [7] and in ACS [8], high-sensitivity C-reactive protein (CRP) in ACS [9], NT-proBNP in ACS [10], and myocardial injury post-PCI).…”
Section: Introductionmentioning
confidence: 99%